Big Book Learning Media Based on Problem Based Learning on the Theme of Togetherness - Ni Putu Yuliana Santini Putri; I Gusti Ayu Tri Agustiana (Mimbar Ilmu, 2023)
The low learning outcomes are influenced by the low interest of students in participating in learning, one of the contributing factors is the lack of use of learning media that is in accordance with student characteristics and learning objectives. This study aims to develop Problem Based Learning Big Book learning media on the theme of togetherness. This research belongs to the type of development research which was developed with the ADDIE model through five stages, namely the analysis, design, development, implementation, and evaluation stages. The subjects involved in this study were material experts, design experts, learning media experts, and 23 students. Data collection in the study was carried out using observation, interviews, questionnaires, and tests. The instrument used is in the form of media validity sheets, as well as multiple choice test questions. The data obtained in the study were then analyzed using correlated t-test analysis techniques. The results of data analysis show that tcount > ttable or 5.23 > 1.68, with the decision being made that if tcount > ttable, then H0 is rejected and H1 is accepted. Based on these results, it can be concluded that the problem-based learning-based big book learning media that was developed is effectively used as a learning medium, which supports the learning process in class so that it can achieve learning goals well and can improve student learning outcomes.